Hubungan Antara Kecerdasan Emosi dengan Self-Control Pada Mahasiswa Psikologi Universitas Muhammadiyah Bandung - Amalia Nafiisah Aliyatul Haq; Irianti Usman Natanegara; Nurlaela Hamidah (LPPAIK Universitas Muhammadiyah Bandung, 2022)
Goleman's marshmallow research illustrates how emotional intelligence is seen through self-control skills. There is a survey in the United States that today's generation is more prone to emotional problems than previous generations. In line with that, researchers found behaviors among psychology students at the Muhammadiyah University of Bandung related to emotional intelligence such as not being confident and not being able to manage the feelings that arise properly. This study aims to determine the relationship between emotional intelligence and self-control in Muhammadiyah University students in Bandung. Used the quantitative-correlational method, a total of 98 respondents consisting of psychology students in the 2018, 2019, 2020 and 2021 batches have been tested on the description of emotional intelligence and self-control through a questionnaire technique. The emotional intelligence questionnaire was created on the theoretical basis of Daniel Goleman, while the self-control questionnaire was created on the theoretical basis of James R Averill. Based on the calculation, the correlational value obtained was rxy = 0.584 with sig = 0.000 (p <0.05). This shows that there is a significant positive relationship between emotional intelligence and self-control in the moderate category. The r2 value of 0.33 means that the Emotional Intelligence variable contributes to Self-Control by 33%. So there are still 67% influenced by other factors not examined in this study. The results of this study indicated that the level of Emotional Intelligence and Self-Control among psychology students at the Muhammadiyah University of Bandung tends to be low. As many as 58.1% of Psychology students at Muhammadiyah University of Bandung are considered to have problems in the ability to recognize emotions, manage emotions and motivate themselves. On the other hand, they have empathy and social skills. In addition, 54.1% of Psychology students at the University of Muhammadiyah Bandung were also considered to have problems in making their own decisions, controlling their behavior and cognitive.